Distinguishing Right Ventricular Cardiomyopathy From Idiopathic Right Ventricular Outflow Tract Tachycardia with T-wave Alternans. (December 2015) - Yalin, Kivanc; Golcuk, Ebru; Aksu, Tolga; Tiryakioglu, Selma K.; Bilge, Ahmet K.; Adalet, Kamil
Abstract: Background: The 2 predominant etiologies of right ventricular tachycardia (VT) are arrhythmogenic right ventricular cardiomyopathy (ARVC) and idiopathic VT arising from the right ventricular outflow tract. Discrimination between these 2 entities is critical, as their prognoses and therapeutic options differ. The microvolt T-wave alternans (TWA) is widely used to predict lethal ventricular arrhythmias in various diseases. However, the clinical significance of TWA in patients with VT originating from the right ventricle has been unknown. This study aims to investigate the possible role of TWA to discriminate ARVC from idiopathic right ventricular outflow tract tachycardia (RVOT-VT). Methods: This study enrolled 38 patients (23 male, 43 ± 16 years) with VT originating from the right ventricle. TWA was measured during exercise testing using the modified moving average method. TWA results were compared among patients with ARVC and RVOT-VT. Results: Twenty-five patients (16 male, 42 ± 16 years) met the Task Force criteria for the diagnosis of ARVC, and 13 patients (7 male, 45 ± 14 years) had idiopathic RVOT-VT. Twenty patients with ARVC had positive TWA test, whereas only 1 patient with RVOT-VT had (80% versus 8%, P < 0.001). Conclusions: In patients with VT of right ventricle origin, positive TWA test supports the diagnosis of ARVC.